Efectos del Covid-19 en el Presupuesto General de la Nación en Colombia - Acero Vaquiro, Sara Milena (Universidad Antonio Nariño, 2021)
The General Budget of the nation for 2020 was approved for 271 billions, just few months after starting its execution, suddenly an unexpected situation appears, a new desease plagues the world, The OMS declares COVID-19 like a global pandemic. This circunstance brought with it public health problems that forced the national goverment to declare health emergency and state of economy emergency, because of that the general Budget result affected, since it was necessary to make Budget additions for $28,77 billions and seek financial sources in order to cover this adds what would increase the fiscal déficit preview for 2020, as a result of this the economy and social development will be affected.